Using Memes to Increase the Students’ Vocabulary Mastery at SMPN 18 Barru - Rahman, Fatur; Talib, Ahmad; Ariyani, Amra (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2025)
The present study strives to figure out whether or not Using Memes Increases the Students' Vocabulary Mastery. The research design used during this research was quantitative with a pre-experimental research type. The population of this research was the entire seventh-grade students at SMP Negeri 18 Barru. The sample was taken by using the cluster random sampling technique, which consists of 25 students of class VIII-1. This experiment was conducted in four meetings. The outcome of the data analysis shows that using memes increases the students' vocabulary mastery. The results of the data analysis exhibited that there was a difference of significant among pre-test results and students' post-test results. That is, the mean score of the students' post-test (83.24) was higher than the students' pre-test means score (30.84). This is also evidenced by the t-test value (26.31), which was higher than the t-table value (2.063899). Based on the findings and discussion of the study, the researcher concludes that using memes increases the students’ vocabulary mastery in class VIII SMPN 18 Barru.